Nursing Education in Canada: Inquiries, Reforms and the Welfare State (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2020)
This article addresses nursing education in Canada, along with two specific reports, Survey of Nursing Education in Canada and Spotlight on Nursing Education, respectively published in 1932 and 1961. The recommendations in these reports, while of great importance and widely disseminated in the nursing world, did not bring about any significant changes to the development of nursing education. This article adopts the welfare state as an analytical framework for illustrating how the political nature of health encouraged the introduction of measures that ultimately culminated in wide-ranging reforms in nursing education designed to meet the objectives of this welfare state.